PEMANFAATAN LIMBAH KONVEKSI UNTUK MENINGKATKAN PENDAPATAN RUMAH TANGGA DI DESA TIMBANG LANGSA KECAMATAN LANGSA BARO - Deasy Amanda Valentine; Feti Priani (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
Solid waste is defined as anything that is not used and is in solid or semi-solid form. In connection with the previous discussion, it is necessary to know the theory of household income or income. This community service activity has the aim of empowering the residents of Timbang Langsa Village, Langsa Baro District so that they can play an active role in overcoming inorganic waste in the form of patchwork. This activity also helps increase household income in Timbang Langsa Village, Langsa Baro District. This goal is realized by providing skills to villagers to use patchwork into corsages/brooches that are suitable for sale. This activity was carried out with the background of wanting to empower community members in Timbang Langsa Village, Langsa Baro District so that they can play an active role in overcoming inorganic waste, in this case patchwork, by recycling. This activity also helps increase household income in Timbang Langsa Village, Langsa Baro District. This goal is realized by providing skills to villagers to use patchwork into corsages/brooches that are suitable for sale.